Three-dimensional numerical simulation of factors affecting surface cracking in double-layer rock mass - Xia, Yingjie; Xue, Xuan; Zhang, Qi; Chen, Jian; Yang, Hai (Frontiers in Earth Science, 2024)
Stratified rock masses comprise various rocks with different thicknesses, lithologies, and compositions. They exhibit unique cracking morphology and failure modes when subjected to external loads. Understanding and mastering the fracture morphology and failure laws of stratified rock masses under three-dimensional mechanical conditions is crucial for researching disasters in underground engineering geology. This paper presents a three-dimensional double-layer rock mass model established using the numerical calculation method based on mesoscopic statistical damage mechanics. The model simulates the cracking mode of the rock surface under biaxial tensile conditions. The simulation results are quantified using PCAS software. Crack indexes, such as the number of cracked blocks, average cracked block area, and surface crack rate, are used to evaluate the degree of influence of different factors on the cracking of the rock surface layer. The results indicate that the degree of surface crack development varies linearly with the degree of homogeneity (m). Additionally, the layer thickness ratio (η) is positively correlated with the average fragmentation area, and the two are logarithmic. Regardless of the model scale, the average circumference of each block is approximately equal to the model side length. The model exhibits the highest degree of crack development when the loads in the x and y directions are equal. Moreover, the degree of crack development in the model is also influenced by the loading per step, and the two are proportional.